1990
DOI: 10.1073/pnas.87.5.1796
|View full text |Cite
|
Sign up to set email alerts
|

Additional polymorphisms at marker loci D9S5 and D9S15 generate extended haplotypes in linkage disequilibrium with Friedreich ataxia.

Abstract: The gene for Friedreich ataxia (FA), a severe recessive neurodegenerative disease, has previously been shown to be tightly linked to the polymorphic markers D9S15 and D9S5 on human chromosome 9. In addition, the observation of linkage disequilibrium suggested that D9S15 is within 1 centimorgan (cM) of the disease locus, FRDA. Although D9SS did not show recombination with F-RDA, its localization was less precise (0-5 cM) due to its lower informativeness. We have now identified additional polymorphisms at both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 15 publications
(14 reference statements)
2
27
0
2
Order By: Relevance
“…Although the number of haplotypes tested is still relatively small, this suggests that unstable alleles derive from LN alleles by recurrent events rather than by a very small number of secondary founder events. On the other hand, the previous finding of significant linkage disequilibrium with markers located 700 to 500 kb from the GAA in French, Italian, Tunisian, Reunion island, and Cajun patients (12,14,36) suggests that such secondary events generating unstable alleles (premutated) are not very frequent. By comparison with estimates made on the age of BRCA1 mutations showing linkage disequilibrium over comparable distances (37), we suggest that the secondary events accounting for the most frequent extended haplotypes seen in FRDA patients of such populations could be at least 30 generations old.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although the number of haplotypes tested is still relatively small, this suggests that unstable alleles derive from LN alleles by recurrent events rather than by a very small number of secondary founder events. On the other hand, the previous finding of significant linkage disequilibrium with markers located 700 to 500 kb from the GAA in French, Italian, Tunisian, Reunion island, and Cajun patients (12,14,36) suggests that such secondary events generating unstable alleles (premutated) are not very frequent. By comparison with estimates made on the age of BRCA1 mutations showing linkage disequilibrium over comparable distances (37), we suggest that the secondary events accounting for the most frequent extended haplotypes seen in FRDA patients of such populations could be at least 30 generations old.…”
Section: Discussionmentioning
confidence: 78%
“…The GAA repeat is moderately polymorphic among normal alleles. The distribution is bimodal; most (83%) alleles contain around nine repeats (7)(8)(9)(10)(11)(12), and 17% are LN alleles of 16 repeats or more. Accurate sizing was determined on 26 SN and 65 LN GAA alleles by denaturing polyacrylamide gel migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary defect underlying the selective cellular degeneration in FRDA remains unknown but the inherited nature of the disease (autosomal recessive) should allow identification ofthe defective gene by positional cloning. The FRDA gene was localized on chromosome 9 in 1988 (2) and extensive genetic and physical mapping of the locus has been done since then (3)(4)(5)(6)(7)(8)(9)(10). These studies showed that the FRDA locus is most tightly linked to the two independently isolated loci D9S5 and D9S15 that lie only 250 kilobases (kb) apart.…”
mentioning
confidence: 99%
“…Only for D9S15 [21,22,27,28] and D9S11 [28] are allele frequencies from other populations known. In all studies at D9S15, allele 3 is more frequent in FRDA chromosomes in contrast to control chromosomes, whereas allele 6 is overrepresented in control chromosomes.…”
Section: Resultsmentioning
confidence: 99%